Whose speeches impact European markets: ECB's or the national central banks'?. (8th September 2021) - Anand, Abhinav; Basu, Sankarshan; Pathak, Jalaj; Thampy, Ashok
Abstract: We quantify the tone from the speeches of the European Central Bank (ECB) as well as that from the national central banks of six leading European nations and analyze its role in explaining the returns of their respective stock market indices. Using recent innovations in financial text analysis, we find evidence that except for France, all nations' stock indices are significantly associated with the tone of speeches delivered by either the national banks or the ECB (or both). For France, the national stock index volatility is found to be associated with its national central bank speech tone.